Pencegahan Stunting Melalui PMT Nasi Woka Dan Puding Kelor Oleh KKN Kolaboratif173 - Mochammad Sahrul Ramadani; Delala Putri Sisiw; Nadilla Retno Anjani; Gerardin Tungga Mahareni; Ulfa Riska Aini; Mir’atus Silviana Putri; Muhammad Zulkifly; Shafa Azelia Ivada; Rofiatul Hikmah; Putri Suqma Suci Rahmawardani; Alifia Damayanti; Hindun Diah Safitri; Siti Roficha; Andre Setiawan; Muhammad Fahrur Rosi; M Haoirul Rofi’i; Fatih Al Fauzi (CV. ITTC INDONESIA, 2024)
Collaborative KKN under the auspices of the Jember Regency Government is a form of service by a group of students from several universities in Jember Regency. One of the villages targeted for Collaborative KKN activities by Group 173 is Subo Village, Pakusari District. One of the main issues being highlighted at this time is the problem of stunting. Group 173 Collaborative KKN students, under the auspices of the Jember District Government, conducted research on the number of young children identified as stunted in Subo Village, Pakusari District. In Subo Village, 25 young children were found to be stunted in 2024. Stunting can be caused by a number of factors, including economic and educational. One form of service that KKN students in Subo Village are providing to the problem of stunting is to conduct socialisation activities to prevent stunting and to provide supplementary nutrition in the form of Woka Rice and Moringa Leaf Extract Pudding to reduce the number of stunted young children in Subo Village, Pakusari District. The methods used in this activity are observation, interview and socialisation. After socialisation on stunting prevention and distribution of PMT (Woka Rice and Moringa Leaf Extract Pudding), it is hoped that it can increase community knowledge and help the village to reduce stunting rates.